Catalytic Enantiodifferentiating Hydrogenation with Commercial Nickel Powders Chirally Modified by Tartaric Acid and Sodium Bromide. Issue 1 (23rd October 2013) - Osawa, Tsutomu; Kizawa, Tomoko; Takano, Fumika; Ikeda, Shinji; Kitamura, Takayuki; Inoue, Yoshihisa; Borovkov, Victor
Abstract The chirally modified nickel catalysts for the enantiodifferentiating hydrogenation of β‐ketoesters are prepared conventionally by immersing hydrogen‐activated metallic nickel into an aqueous solution of enantiopure tartaric acid, in which the preactivation of nickel is essential. Herein, we revealed that even commercially available nickel powders without any pretreatment can catalyze the enantiodifferentiating hydrogenation of β‐ketoesters to give the corresponding β‐hydroxyesters in quantitative yield and high enantioselectivity (up to 91 %) under optimized conditions. The immediate use of commercially available nickel powders and the reproducible high chemical and optical yields not only expand the scope of heterogeneous asymmetric catalysis but also pave the way for the practical application and industrial use of chirally modified nickel catalysts.